2016
DOI: 10.1016/j.neuint.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway metabolism following prenatal KMO inhibition and in Mecp2+/− mice, using liquid chromatography-tandem mass spectrometry

Abstract: To quantify the full range of tryptophan metabolites along the kynurenine pathway, a liquid chromatography – tandem mass spectrometry method was developed and used to analyse brain extracts of rodents treated with the kynurenine-3-mono-oxygenase (KMO) inhibitor Ro61-8048 during pregnancy. There were significant increases in the levels of kynurenine, kynurenic acid, anthranilic acid and 3-hydroxy-kynurenine (3-HK) in the maternal brain after 5 h but not 24 h, while the embryos exhibited high levels of kynurenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…We were unable to measure the terminal metabolites—xanthurenic acid, quinolinic acid, and picolinic acid—that have previously been detected by this tandem mass spectrometry method in brain samples [ 19 ]. CSF levels of xanthurenic acid were <0.5 nmol/L, and accurate quantification would require the concentration of larger sample volumes prior to analysis..…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to measure the terminal metabolites—xanthurenic acid, quinolinic acid, and picolinic acid—that have previously been detected by this tandem mass spectrometry method in brain samples [ 19 ]. CSF levels of xanthurenic acid were <0.5 nmol/L, and accurate quantification would require the concentration of larger sample volumes prior to analysis..…”
Section: Resultsmentioning
confidence: 99%
“…Tandem mass spectrometry parameters were as follows: curtain gas, 45; CAD gas, medium; ion source voltage, −4500 V; gas temperature, 400°C; gas 1, 30; and gas 2, 30. Full details of mass spectrometry conditions are described by Forrest et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this KMO inhibitor also managed to increase 3-HK and QUIN levels in the rat striatum moderately [97]. Ro61-8048 is another experimental inhibitor of KMO that has been shown to substantially increase KYNA levels in the brain by more than 10-fold [98][99][100]. Another KMO inhibitor, meta-nitrobenzoyl alanine, has been studied widely [101,102] and is associated with markedly elevated levels of KYNA in the rat brain (nearly 5 times more than the baseline).…”
Section: Kmo Inhibitorsmentioning
confidence: 99%
“…Although RTT is more often classified as a neurodevelopmental disorder, recent studies in cytokine release also suggest involvement of the immune system [49]. A previous study demonstrated that during early brain formation disturbances in the metabolism produces changes in the morphological and biochemical development of the brains [50]. Another study further observed that models with synaptic defects during development fail to couple to metabolic pathways [51].…”
Section: Robust Protein Profile Changes Along the Course Of Neuronal mentioning
confidence: 99%